Anti‐interleukin‐33 inhibits cigarette smoke‐induced lung inflammation in mice. Issue 1 (13th December 2012) - Qiu, Chuan; Li, Yan; Li, Mingcai; Li, Min; Liu, Xiaojin; McSharry, Charles; Xu, Damo
Summary: The mechanism by which cigarette smoke (CS) causes chronic obstructive pulmonary disease (COPD) is poorly understood. Interleukin‐33 (IL‐33) is a pleiotropic cytokine predominantly expressed in lung tissue and can elicit airway inflammation in naive mice. We tested the hypothesis that IL‐33 is induced by CS and contributes to CS‐mediated airway inflammation in a mouse model of CS‐induced COPD. Groups of mice were exposed to CS three times per day for 4 consecutive days. The expression levels of IL‐33 and ST2 were markedly enhanced in the lung tissue of mice inhaling CS. Exposure to CS also induced neutrophil and macrophage infiltration and expression of inflammatory cytokines (IL‐1β, tumour necrosis factor‐α, IL‐17), chemokines (monocyte chemoattractant protein‐1) and mucin 5, subtypes A and C in the airways. More importantly, all of these CS‐induced pathogenic changes were significantly inhibited by treatment with neutralizing anti‐IL‐33 antibody delivered intranasally. Hence, our results suggest that IL‐33 plays a critical role in CS‐mediated airway inflammation and may be a therapeutic target in CS‐related diseases, including COPD.